Perspectives for the Next Generation of Virus Research: Spearheading the Use of Innovative Technologies and Methodologies - Takatoki Yamamoto (Frontiers Research Topics, 2017)
Infectious diseases are associated with approximately 20% of global mortality, with viral diseases causing about one third of these deaths. Besides newly emerging and re-emerging viral infections will continue to pose a threat to human survival globally. In this case scientific advances have greatly been increased to defend against those pathogens. For example, rapid genomic sequencing, proteomics, epigenomics, nanotechnology, and other advanced tools are being applied to detect viruses at the point of care and to track their spread within human populations as well as to understand virus-host interaction and virus induced pathogenesis. From rapid identification of new viruses to prevention with vaccination and treatment with effective therapeutics, biomedical research has continuously provided tools to meet the constant threat of emerging viral pathogens. Despite these advances, each new disease brings unique challenges to scientists every year. So we must stay at the cutting edge of scientific discovery, working energetically to develop new tools to combat the ever-changing threats they pose. Our research topic highlights such advanced and new technology based virus research which definitely bolsters the researcher's ability to tackle emerging, re-emerging and stable viral pathogens. We are credulous that the papers including in the e-books will be beneficial to the experts in the field to understand the molecular, immunological, ecological and clinical aspects of the next generation researches for the prevention and control of infectious diseases caused by viruses.